A patient with autosomal recessive Alport syndrome due to segmental maternal isodisomy - Fu, Xue J (Hum Genome Var, 2014)
We report the case of a 22-year-old male with autosomal recessive Alport syndrome. Molecular analysis showed that this patient has a homozygous missense (NM_000091.4:c.3266G>A) Gly1089Asp mutation in the COL4A3 gene. The proband inherited the mutation from his heterozygous carrier mother, whereas the father carried only wild-type alleles. We performed comparative genome hybridization and single-nucleotide polymorphism microarray analyses and confirmed that there was partial maternal isodisomy.